Pertumbuhan, biomassa, dan kandungan pigmen Thalassiosira sp. pada media kultur yang berbeda - Arifin, Nasrullah Bai; Febiana, Arifatus; Supriatin, Febriyani Eka; Fakhri, Muhammad (Jurnal Sumberdaya Akuatik Indopasifik, 2025)
Microalgae is a photosynthetic microorganism that oftenly used as live feed for aquaculture. One of the species that mostly used is Thalassiosira sp. This species belongs to the group of diatom which has high nutritional content. The availability of nutrient in media is one of the main factor affecting growth and biochemical content of Thalassiosira sp. This study aimed to evaluate effect of cultivation media on the growth, biomass, and pigment content of Thalassiosira sp. This research consisted of four treatments and four replicates. The treatments included different cultivation media namely walne, Blue Green-11 (BG-11), Bold’s Basal Medium (BBM), dan f/2 (Guillard). During the study, growth was observed daily while biomass and pigment content were evaluated at the early stationary phase. The result showed that different culture media was significantly (p < 0.05) effect the growth, biomass, and pigment content of Thalassiosira sp. The walne medium produced highest growth, biomass, and pigment content. On the other hand, the lowest production of growth, biomass, and pigment content were obtained in BBM. This study indicated that the suitable medium for Thalassiosira sp. cultivation was walne.